2022
DOI: 10.20473/jbe.v10i12022.86-94
|View full text |Cite
|
Sign up to set email alerts
|

Nutrition as a Risk Factor of Child Leprosy in Gresik District 2019

Abstract: Background: Indonesia's annual increase in leprosy is a serious health problem. In east Java, child leprosy cases spread in several counties/cities, the number of new cases of child leprosy cases has been raised in Gresik District from 2015 until 2019. Purpose: This study analyzed characteristics, BCG vaccine status, nutritional status and home environment, the correlated risk factors to child leprosy in Gresik District. Methods: This study used a design population-based matched case-control design and analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 16 publications
1
2
0
Order By: Relevance
“…Similar to three studies conducted in Gresik, Indonesia, which found a relationship between the history of receiving the BCG vaccine and the incidence of leprosy in children (13)(14)(15). Prior BCG vaccination is shown to be a strong predictor, which means that the children who did not undergo BCG immunization have an OR exp (B) of 22,164 times to contract leprosy (14).…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Similar to three studies conducted in Gresik, Indonesia, which found a relationship between the history of receiving the BCG vaccine and the incidence of leprosy in children (13)(14)(15). Prior BCG vaccination is shown to be a strong predictor, which means that the children who did not undergo BCG immunization have an OR exp (B) of 22,164 times to contract leprosy (14).…”
Section: Discussionsupporting
confidence: 81%
“…Prior BCG vaccination is shown to be a strong predictor, which means that the children who did not undergo BCG immunization have an OR exp (B) of 22,164 times to contract leprosy (14). A study explains that access to health services is still an obstacle to administering the BCG vaccine (13), in line with research that mentions leprosy transmission factors in children can be seen from the coverage of the BCG vaccine program that is imperfect (16). The study conducted found a statistical relationship, but in the study 26 people who had leprosy and had a history of BCG vaccination, more than respondents who did not have a history of BCG vaccination but had leprosy.…”
Section: Discussionmentioning
confidence: 99%
“…Leprosy is a type of chronic disease, namely a disease with a long latency period. This long latency period makes the prevalence of leprosy at a young age tend to be small (15). Leprosy has an incubation period of 2-5 years from when a person becomes infected.…”
Section: Age Relationship With Leprosy Incidencementioning
confidence: 99%